Determinants of Economic Growth in Five Countries With the World Highest Population - Putri, Naswa Berliana; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2026)
Economic growth is an important indicator in describing the increase in a country’s output, especially in countries with the highest populations in the world, namely India, China, United States, Indonesia, and Pakistan. This study aims to analyze the effect of corruption control, digital technology, education, investment, capital accumulation, and trade openness on economic growth during the 2013-2023 period using panel data regression. The results show that control of corruption, digital technology, and capital accumulation have a positive and significant effect on economic growth, while education, investment, and trade openness do not show a significant effect. These findings confirm that strengthening institutional quality, utilizing digital technology, and increasing capital accumulation remain key factors in driving economic growth in countries with large populations.